2021
DOI: 10.3390/cancers13164183
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Meningiomas: Influence of Cord Compression and Radiological Features on Preoperative Functional Status and Outcome

Abstract: Background: Radiological parameters predicting the postoperative neurological outcome after resection of a spinal meningioma (SM) are poorly studied, with controversial results. Methods: Observational multicenter cohort (2011–2018) of adult patients undergoing surgery for resection of SM. Tumor-canal volume ratio (TCR), the areas related to the cord and tumor occupancy at maximum compression, the presence of dural tail, calcifications, signs of myelopathy, and postoperative cord expansion were compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Three studies only including adults (>18 years) reported 28 cases among 3063 patients (0.9%) [ 4 , 55 , 56 ]. The lower percentage in these studies may indicate that a significant number of these patients are diagnosed before reaching adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies only including adults (>18 years) reported 28 cases among 3063 patients (0.9%) [ 4 , 55 , 56 ]. The lower percentage in these studies may indicate that a significant number of these patients are diagnosed before reaching adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have explored the relationship between tumor dimensions, cord compression, and functional outcome and/or preoperative neurological impairment, and results have been conflicting [ 6 , 10 , 43 , 44 ]. In our series, we found a significant correlation between preoperative spinal cord compression (measured as TCR) and functional impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Even though spinal meningiomas (SM) are rare, they are among the most frequent intradural extramedullary tumors, representing about 1.2–12% of all meningiomas. SM constitute one-third of primary spinal tumors and 25–46% of all intradural spinal tumors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations